Utilizing Interactive Molecular Simulations to Improve Chemical Bonding Comprehension among Computer Technology Majors - Danila, Jane; Mellona, Jonathan; Peria, Jo Neil (International Journal of Sustainability and Advanced Integrated Research, 2026)
The mastery of fundamental chemistry concepts, particularly molecular geometry and chemical bonding, remains a formidable pedagogical challenge within technical-vocational curricula. This study determined the effectiveness of Simulation-Aided Learning (SAL) using PhET Interactive Simulations to improve the ability of thirty-six (36) BIndTech – Computer Technology students to predict molecular shapes and polarities. Utilizing a quasi-experimental one-group pretest-posttest design, the researchers implemented a four-week "Digital Chemistry" series. Results indicated a substantial performance increase, with mean scores rising from 21.50 (43%) to 44.20 (88.4%). Statistical analysis through a Paired Samples T-test confirmed that the improvement was directly attributable to the intervention. Students expressed high satisfaction with an overall weighted mean of 4.71, indicating that 3D digital visualization effectively overcomes the spatial limitations of static textbooks. This study addresses United Nations Sustainable Development Goal (SDG) 4: Quality Education, by enhancing technical-vocational pedagogy through digital innovation to ensure inclusive and effective learning outcomes for technology-oriented students.